A Comprehensive Study of Security in Cloud Computing - Bhatia, Manjot Kaur; Bhardwaj, Akash; Singla, Diksha (International Journal of Computer Sciences and Engineering, 2018)
Cloud computing has become a popular model for reducing cost of business, improvise quality of services, and provide good & secure computing. It opens up the Computing World by providing the access to anything and anywhere through Internet. It acts as a spectrum of substantial interest among IT professionals, technocrats & business leaders due to these proven potentials. Numerous emerging computing paradigms database outsourcing serves as future advantages of cloud computing. With the increasing speed of its popularity, many security questions are arising with their respective solutions aiming to give a better understanding of their complex scenario, in this paper we will provide a comprehensive view over security in context of cloud computing and also provide a view of current status of security at present. To start with, we'll take a look at various Cloud computing models, cloud computing deployment models, key issues in security along with challenges in provocation of permissions to various platforms.